The IAC Model Approach as an Effort to Increase Early Awareness of Gasoline Disease Risk at Mini Pom Operators in Depok City - Omega DR Tahun; Nofa Anggraini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The number of mini poms (pertamini) in parts of Indonesia certainly has a good impact on the distribution of fuel. However, adverse effects also accompany, one of which is the safety and health aspects. Types of health effects that occur / diseases caused by gasoline (PAB), are dizziness, nausea, vomiting, hypertension, cancer, throat cancer and sudden sniffing death. The purpose of this study is to increase early awareness of the risk of diseases caused by gasoline through the IAC model (Identification - action - prevention) at the mini pump operators in the city of Depok.the type of method used in this study is divided into 2 parts, namely the first is an analytical observational (survey) study with a cross sectional study design and the type of statistical test used is the t test (t test), the total sample of 127 respondents. Whereas in the second part is action research in the form of the implementation of health education in the distribution of masks to mini operators to be used as PPE (personal protective equipment) when working. Statistical tests show that there are differences in behavior to be aware of diseases caused by gasoline in respondents who lack knowledge and good (p value = 0,000), furthermore the attitude variable is also that there are differences in behavior between respondents who have negative and positive attitudes (p value = 0.027).health education is needed for mini pump operators to improve their knowledge and the need for regulations issued by the government to regulate the use of masks when in direct contact with gasoline.